Oncogenic B-Myb Is Associated With Deregulation of the DREAM-Mediated Cell Cycle Gene Expression Program in High Grade Serous Ovarian Carcinoma Clinical Tumor Samples - Iness, Audra N.; Rubinsak, Lisa; Meas, Steven J.; Chaoul, Jessica; Sayeed, Sadia; Pillappa, Raghavendra; Temkin, Sarah M.; Dozmorov, Mikhail G.; Litovchick, Larisa (Frontiers in Oncology, 2021)
Cell cycle control drives cancer progression and treatment response in high grade serous ovarian carcinoma (HGSOC). MYBL2 (encoding B-Myb), an oncogene with prognostic significance in several cancers, is highly expressed in most HGSOC cases; however, the clinical significance of B-Myb in this disease has not been well characterized. B-Myb is associated with cell proliferation through formation of the MMB (Myb and MuvB core) protein complex required for transcription of mitotic genes. High B-Myb expression disrupts the formation of another transcriptional cell cycle regulatory complex involving the MuvB core, DREAM (DP, RB-like, E2F, and MuvB), in human cell lines. DREAM coordinates cell cycle dependent gene expression by repressing over 800 cell cycle genes in G0/G1. Here, we take a bioinformatics approach to further evaluate the effect of B-Myb expression on DREAM target genes in HGSOC and validate our cellular model with clinical specimens. We show that MYBL2 is highly expressed in HGSOC and correlates with expression of DREAM and MMB target genes in both TCGA as well as independent analyses of HGSOC primary tumors (N=52). High B-Myb expression was also associated with poor overall survival in the TCGA cohort and analysis by a DREAM target gene expression signature yielded a negative impact on survival. Together, our data support the conclusion that high expression of MYBL2 is associated with deregulation of DREAM/MMB-mediated cell cycle gene expression programs in HGSOC and may serve as a prognostic factor independent of its cell cycle role. This provides rationale for further, larger scale studies aimed to determine the clinical predictive value of the B-Myb gene expression signature for treatment response as well as patient outcomes.